2020
DOI: 10.1177/2158244020929311
|View full text |Cite
|
Sign up to set email alerts
|

Does Culture Matter? A Comparative Study on the Motivations for Online Identity Reconstruction Between China and Malaysia

Abstract: On social network platforms, people may reconstruct an identity due to various reasons, such as vanity, disinhibition, bridging social capital, and privacy concerns. This study aims to identify cultural differences in the motivations for online identity reconstruction between China and Malaysia. Data were collected from China and Malaysia using an online survey. A total of 815 respondents (418 Chinese and 397 Malaysians) participated in this study. Differences were found not only between Chinese and Malaysian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 102 publications
1
7
0
Order By: Relevance
“…Meanwhile, linguistic proximity is another predictor positively linked to purchase behaviour towards Chinese films among Chinese Malaysians. In line with previous theoretical and empirical studies [9,11], the present research posits the significance of cultural proximity in media products. First, language ability determines the extent to which consumers can understand the central meaning of films expressed by filmmakers.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Meanwhile, linguistic proximity is another predictor positively linked to purchase behaviour towards Chinese films among Chinese Malaysians. In line with previous theoretical and empirical studies [9,11], the present research posits the significance of cultural proximity in media products. First, language ability determines the extent to which consumers can understand the central meaning of films expressed by filmmakers.…”
Section: Discussionsupporting
confidence: 78%
“…Watching Chinese films is a source of enjoyment and relaxation for many Chinese Malaysians, as well as a method to strengthen one's sense of connection to one's motherland. Given the cultural proximity between China and Malaysia [9], the Malaysian film industry's purchase behaviour towards Chinese films could be influenced by cultural components used in cinema, such as linguistic proximity, which refers to the similarity in the language used in cultural products [10,11]. For example, linguistic proximity may influence movie ticket purchases, TV channel subscriptions, and media streaming service memberships.…”
Section: Introductionmentioning
confidence: 99%
“…Gender and cultural differences were salient in the motivations for online identity reconstruction ( Valkenburg et al, 2005 ; Huang et al, 2020 ). For example, it is found that when compared with Chinese social network users, Malaysian users were more likely to reconstruct their identity due to privacy concerns ( Huang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gender and cultural differences were salient in the motivations for online identity reconstruction ( Valkenburg et al, 2005 ; Huang et al, 2020 ). For example, it is found that when compared with Chinese social network users, Malaysian users were more likely to reconstruct their identity due to privacy concerns ( Huang et al, 2020 ). Girls placed more emphasis on self-exploration and social compensation than boys ( Valkenburg et al, 2005 ), while boys were more likely to be motivated by social facilitation ( Ceyhan, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Literat (2021) observed in a study on computer subcultures, the focus was not so much on what people were doing with computers but rather how their interactions with computers led them to think differently, to feel differently, to relate differently, this was referred to as a 'romantic reaction' to computers. Computers have been helpful in showing us just how multifaceted and not one dimensional our lives are (Huang et al, 2020). New communication technologies have freed interaction from the requirements of physical co-presence and created an online presence and structure that cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%